P-74 Harnessing leadership potential in the hospice. Issue Volume 9: Issue (2019)Supplement 4 (17th November 2019) - Stone, Jackie; Dey, Nick
Abstract : Background: As part of a strategic plan a hospice in Scotland invested in a Leadership and Management Development programme for clinical and non-clinical staff which was delivered over three years. This was based upon the principle that professionals require a combination of leadership and management skills in order to ensure the services they provide are of the highest quality and person-centred. We believe that leadership and management skills are required at all levels in the hospice to ensure that each department and/or team continuously works to achieve the strategic and operational objectives of the hospice. In essence leadership skills are not just for those at a very senior level. Aims: To develop leadership and management skills within the hospice to support and ensure that each department and/or team continuously works to achieve the strategic and operational objectives of the hospice; To enable true staff engagement with implementation of the hospice's strategic objectives. Method: Three programmes were delivered over three years with each programme lasting for twelve months and thirty staff members participating in total. The underpinning philosophy of the programme is based on person-centeredness with each individual bringing their own unique set of skills and previous experiences into the programme. The programme consisted of a number of different elements: workshops, action learning sets, 360 degree feedback on their leadership behaviours and the opportunity to lead on a specific service or practice development project relevant to their role. Results: Evaluation demonstrated that participants developed their abilities in: self–awareness, self–management and personal development; developing and enhancing person–centred services and care; managing effective relationships with team members within the hospice; networking and partnership working. In addition participants designed and led a quality improvement project specific to their own area of work which supported the implementation of the hospice strategy.